EFL Students' Needs of Digital Literacy to Meet the Demands of 21stCentury Skills - ERYANSYAH ERYANSYAH; ERLINA ERLINA; FIFTINOVA FIFTINOVA; ARI NURWENI (Universitas Jambi, Indonesia, 2019)
This study was a survey study which was aimed at looking at EFL students’ current knowledge and skills of ICT. The research questions of this study were(1) What levels of digital literacy are the EFL students?, (2) What are the factors affecting EFL students in using ICT in language learning?, and (3) What are the students' needs to improve their digital literacy skills to meet the demands of the 21st century skills? Two groups of EFL students from two state-owned universities in the southern part of Sumatra were involved in this study. A set of questionnaires adapted from Ravitz (2014) was used. The findings showed that EFL students’ current level of digital literacy was categorized low. Factors affecting them from using ICT in language learning properly were limited use of ICT applications as a tool for language learning and limited access to computers and internet applications on campus. What the EFL students needed to improve their digital literacy skills was the availability of computers with internet applications to be used anytime on campus, ICT training for both teachers and students, and continuous integration of ICT in language learning.